2014
DOI: 10.6002/ect.2013.0218
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Objectives: Giant cell myocarditis is a rare and often fatal disorder. According to the American Heart Association, the American College of Cardiology Foundation, and the European Society of Cardiology scientific statements, an endomyocardial biopsy should be done to exclude giant cell myocarditis in unexplained new-onset heart failure of 2 weeks to 3 months duration associated with dilated left ventricle and new ventricular arrhythmias, or Mobitz type II second-degree, or third-degree atrioventricular heart b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 17 publications
(21 reference statements)
0
2
0
Order By: Relevance
“… 1 However, studies have shown that high-degree atrioventricular block and ventricular arrhythmias may be absent up to 50% of the time. 1 , 7 Therefore, a rapid decline in LVEF over several days, with subacute CHF of 2 weeks' to 3 months’ duration that is refractory to 1 to 2 weeks of standard treatment, should raise suspicion for GCM. An endomyocardial biopsy should be considered—including early transfer to specialized centres when necessary—in these circumstances, irrespective of vaccination status, and even in the absence of arrhythmia and classic echocardiographic features of GCM.…”
Section: Discussionmentioning
confidence: 99%
“… 1 However, studies have shown that high-degree atrioventricular block and ventricular arrhythmias may be absent up to 50% of the time. 1 , 7 Therefore, a rapid decline in LVEF over several days, with subacute CHF of 2 weeks' to 3 months’ duration that is refractory to 1 to 2 weeks of standard treatment, should raise suspicion for GCM. An endomyocardial biopsy should be considered—including early transfer to specialized centres when necessary—in these circumstances, irrespective of vaccination status, and even in the absence of arrhythmia and classic echocardiographic features of GCM.…”
Section: Discussionmentioning
confidence: 99%
“…In later stages, the Th2 response may dominate, leading to the fibrosis of affected areas. The eosinophils in the infiltrate also increase cytokine production and release cytotoxic substances from their granules, like major basic proteins and eosinophil peroxidase [ 17 ].…”
Section: Reviewmentioning
confidence: 99%